The Downfall of Sports Science in the United States - Stone, M. H.; Sands, W. A.; Stone, M. E. (Strength and Conditioning Journal, 2004)
Although sports are considered an important part of American life, sports science has lost its identity and has largely been replaced by exercise science. Although exercise science may use sport for examples or as handy models for understanding exercise responses, exercise science is seldom concerned with enhancing the sport performance of the athletes it studies. The authors hope that sport science may be resurrected so that modern American athletes can benefit from scientifically derived and tested training methods and thus compete more effectively both at home and abroad.